Broken and Disordered: Selected Critical Readings on Broken Windows Policing. Issue 3 (2nd October 2017) - Davis, Helane E.
ABSTRACT: Broken windows policing came of age when one of the nation's largest and most high-profile police departments began to systematize the philosophy as part of order maintenance policing. This bibliography, comprised primarily of selected readings critical of the phenomenon, not only illustrates the depth and breadth of the criticism of specific order maintenance methods but questions much of the "proof" of their effectiveness. Book-ending the critiques are readings that articulate the founding "broken windows" theory, and cases that provide the legal framework for this particular intersection between social norms theory and law.